ENVIRONMENTAL POLICIES AND MANAGEMENT IN INDIA - Chelani, Gomti (International Journal of Research -GRANTHAALAYAH, 2015)
In this Universe the Earth is the only planet where life is possible. Modernization and industrialization affect nature in 2 ways. Firstly it is extremely destructive of environment in its search for inexpensive biomass-based raw materials and for the opportunities for waste disposal. Secondly modernization is transforming the very character of nature. The tendency is to reduce the diversity in nature and transform it in to high yielding monocultures. India is country with a high level of population density. In the name of economic development often any human activity, which results in the destruction of an ecological space or in its transformation, is justified. Environmental issues were completely overlooked during the first 2 decades of economic development. Government realized the need for environmental protection in early 1970s. Environmental protection was adopted as directive principles of state policy in our Constitution. The protection of environment is also a fundamental duty of every citizen of India. Presently there are about 30 major enactments related to protection of environment being administered by the Central and State Governments. The problems concerning the policies of Government related to environmental protection and the implementation of various laws are discussed in this paper. India’s biggest challenge today is to identify and implement development process that will lead to greater equity, growth and sustainability. To achieve these goals Government policies should be reformed and it is our duty to come forward and make these policies successful.